Psikoedukasi Work Alienation melalui FGD dan Pamflet pada Karyawan Pertambangan - Irham Habibi Fanindra; Nida Hasanati (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Employees at PT Kita Tambang Mineral are at risk of experiencing work alienation due to the demanding nature of mining operations, roster-based work schedules, remote work locations, and limited social interaction. These conditions reduce work engagement, diminish employees' sense of meaning at work, and negatively affect their psychological well-being and work productivity. This study aimed to implement and evaluate a psychoeducational program as a preventive intervention to improve employees' understanding of work alienation while reducing their level of work alienation in the workplace. The program involved 28 employees of PT Kita Tambang Mineral and was conducted using two intervention methods, namely Focus Group Discussions (FGDs) and educational pamphlets. Program effectiveness was evaluated using pre-test and post-test assessments, and the data were analyzed descriptively by comparing participants' knowledge and work alienation levels before and after the intervention. The findings indicated that both intervention methods successfully improved employees' understanding of work alienation and reduced their levels of work alienation. However, the FGD approach proved to be more effective than the pamphlet-based intervention because it encouraged active participation, facilitated experience sharing, strengthened social support among employees, and increased participant engagement throughout the program. Overall, the psychoeducational program provides practical benefits for the company by promoting workplace mental health, strengthening communication and social connectedness among employees, and supporting the creation of a healthier, more productive, and sustainable work environment.